2023
DOI: 10.1021/acsami.2c21866
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Nanoparticles Embedded in Chemical-Expanded Graphite through Electrostatic Attraction for High-Performance Lithium-Ion Batteries

Abstract: Silicon (Si) is a promising next-generation anode for high-energy-density lithium-ion batteries. The application of silicon/carbon (Si/C) composites with high Si content is hindered by the huge volume change and insecure electrochemical interface of the Si anode. Herein, chemical-expanded graphite (CEG) is used as a carbon matrix to form Si@CEG/C composites with an embedded structure. CEG with an abundant pore structure and electropositivity can well disperse and accommodate a mass of Si nanoparticles (Si NPs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…After 10 cycles, however, the R ct values decrease and show no obvious change with increasing cycles, manifesting high conductivity, low interfacial resistance, and stable electrode structure and SEI film. 63,64 In contrast, after 10 cycles, the R ct values of the Si electrode continue to increase with increasing cycles. It indicates that the electrode structure is unstable, and the formed electrode fracture causes the constant generation of new exposed surfaces of active materials, which results in the unstable SEI film to grow continuously, and the electronic and ionic conductive pathways are severely deteriorated.…”
Section: Resultsmentioning
confidence: 95%
“…After 10 cycles, however, the R ct values decrease and show no obvious change with increasing cycles, manifesting high conductivity, low interfacial resistance, and stable electrode structure and SEI film. 63,64 In contrast, after 10 cycles, the R ct values of the Si electrode continue to increase with increasing cycles. It indicates that the electrode structure is unstable, and the formed electrode fracture causes the constant generation of new exposed surfaces of active materials, which results in the unstable SEI film to grow continuously, and the electronic and ionic conductive pathways are severely deteriorated.…”
Section: Resultsmentioning
confidence: 95%
“…The phase composition of the composite was further studied through X-ray diffraction (XRD) patterns. As shown in Figure 2 a, all composites exhibit diffraction peaks of crystalline Si at 2θ = 28.5°, 47.7°, 56.2°, 69.2°, and 76.3°, corresponding to the (111), (220), (311), (400), and (331) planes of Si [ 33 ], respectively. In the Si@SnO 2 composite, characteristic peaks of SnO 2 appear at 2θ = 26.5°, 33.8°, and 51.7°, corresponding to the (110), (101), and (211) planes of SnO 2 [ 34 ], respectively, indicating that a layer of SnO 2 is successfully coated on the surface of Si through the annealing process.…”
Section: Resultsmentioning
confidence: 99%
“…To deal with the problems caused by volume change, extensive efforts have been devoted to the design of reasonable Si nanostructures, including nanoparticles, , nanowires, , and nanotubes. , It has been revealed that, during the lithiation and delithiation processes, Si particles having a critical size of less than 150 nm will not fracture or pulverize . The fabrication methods of nanostructured Si include chemical vapor deposition, magnesiothermic reduction reaction, , laser ablation, , and ball milling. Among these methods, ball milling is cost-effective, easy for mass production, and much more possible for commercial application.…”
Section: Introductionmentioning
confidence: 99%